(untitled) (Research, Society and Development, 2022)
Water resources play an important role in the maintenance of human life, and, therefore, the relationship between human health and the quality of water distributed to society has been increasingly discussed. To be considered adequate for the health of the human population, water must comply with microbiological and physical-chemical parameters indicated by the Ministry of Health for human consumption, indicating its reasons and importance. Literature reviews were performed in Google Scholar and Scientific Electronic Library Online (SciELO) databases. After careful evaluation of the articles, a total of 28 were selected for the development of this work. The results indicated that the most used parameters to assess the potability of water were physical, followed by chemical and microbiological, and that these directly implied in the diagnosis of water quality. Thus, through this study, it can be concluded that it is essential to have water purity parameters, as well as physical, chemical, and microbiological analyzes to assess and guarantee the quality of water, in addition to preventing diseases from being transmitted by transmission water.